1994
DOI: 10.1007/bf02350060
|View full text |Cite
|
Sign up to set email alerts
|

Worker's genetic diversity has no relation to pollen diversity in a honey bee colony (Apis mellifera L.)

Abstract: --No differences were observed between the species diversity of pollen gathered by colonies with artificially reduced worker genetic diversity and those derived from naturally mated queens. Such a result does not support the hypothesis that polyandry increases colony fitness in which a genetic basis is created for using a wider range of food sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Nevertheless, the caste system hypothesis is unlikely to explain the origin of polyandry, because morphological differentiation among workers should take a long time to evolve. Furthermore, Woyciechowski and Warakomska (1994) showed that even in honeybees, genetic diversity between workers had no effect on the division of labor, and several authors have indicated that there is no convincing evidence that honeybee colonies with greater genetic diversity have higher survival or reproduction than those with low diversity (Oldroyd et al 1991(Oldroyd et al , 1993(Oldroyd et al , 1994Fuchs and Schade 1994). Therefore, it is difficult to explain the evolution of polyandry in eusocial Hymenoptera using this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the caste system hypothesis is unlikely to explain the origin of polyandry, because morphological differentiation among workers should take a long time to evolve. Furthermore, Woyciechowski and Warakomska (1994) showed that even in honeybees, genetic diversity between workers had no effect on the division of labor, and several authors have indicated that there is no convincing evidence that honeybee colonies with greater genetic diversity have higher survival or reproduction than those with low diversity (Oldroyd et al 1991(Oldroyd et al , 1993(Oldroyd et al , 1994Fuchs and Schade 1994). Therefore, it is difficult to explain the evolution of polyandry in eusocial Hymenoptera using this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The differences found in these studies relate to foraging behaviour or apply to unnaturally small colonies, and do not directly address colony per formance. Woyciechowski & Warakomska (1994) showed that worker genetic diversity had no effect on the diversity of pollen collected. Evidence on this issue may also suffer from complications due to non-additive genetic effects.…”
Section: (C) D Ivision O F Labourmentioning
confidence: 99%
“…While a number of studies support a strong influence of kin structure in some contexts (e.g., Trivers and Hare 1976;Peters et al 1999;Reeve et al 2000;Tarpy 2003), others have failed to detect a clear association between social and genetic structure (e.g., Woyciechowski and Warakomska 1994;Heinze 1995;Brown and Keller 2000;Hammond et al 2003). In the following, we describe how kin structure is expected to affect life history traits in social Hymenoptera and briefly examine the evidence for or against such an influence.…”
Section: Haplodiploidy and Eusocialitymentioning
confidence: 99%
“…However, this apparent specialization does not always directly result in a benefit for polyandrous colonies. For example, in some studies, the genetic diversity of a colony had no effect on pollen diversity (Woyciechowski and Warakomska 1994), honey yield, or colony size (Neumann and Moritz 2000). In another study, multiple mating was found to be associated with larger pollen and honey stores and a higher production of sexuals (Fuchs and Schade 1994).…”
Section: Kin Structure Division Of Labor and Disease Resistancementioning
confidence: 99%